Implementasi Prosedur Kerja Pengawas PAI Sekolah Dasar di Kabupaten Sarolangun - Mohamad Muspawi (Universitas Batanghari Jambi, 2018)
This study aims to determine the empirical condition of the implementation of work procedures for PAI supervisors of primary schools in Sarolangun District. The specific target to be achieved is: 1). Knowing the implementation of the PAI supervisory work procedures for elementary schools in Sarolangun District. 2). Knowing the constraints and solutions for implementing work procedures for PAI supervisors for primary schools in Sarolangun District. Knowing the constraints and solutions for implementing work procedures for PAI supervisors for primary schools in Sarolangun District. The research method used is a qualitative descriptive method, in which the researcher describes the findings of the research in a narrative and what it is. Data collection techniques used are observation techniques, documentation, and interviews. To check the validity of the data, the author makes persistence observation, triangulation, member check, audit trail. And to analyze the data, the authors conduct data review and reduction, data unitization, data categorization, and data interpretation. The results of the study show that: 1. The implementation of the work procedures of elementary school PAI supervisors in Sarolangun district is as follows: a. Get a letter of assignment. b. Visiting the location and conducting coaching. c. Make work reports and submit them to superiors. 2. Constraints and solutions for implementing PAI supervisory work procedures for primary schools in Sarolangun District are as follows: a. Lack of personnel. The solution is by utilizing the MGMP moment b. The distance to some schools is quite far. The solution is to visit the nearest school. c. Access to several schools is quite difficult. The solution is to visit schools that are easily accessible.